Naturalization of introduced plants: ecological drivers of biogeographical patterns - Richardson, David M; Pyšek, Petr (The New phytologist, 2012)
The literature on biological invasions is biased in favour of invasive species--those that spread and often reach high abundance following introduction by humans. It is, however, also important to understand previous stages in the introduction-naturalization-invasion continuum ('the continuum'), especially the factors that mediate naturalization. The emphasis on invasiveness is partly because most invasions are only recognized once species occupy large adventive ranges or start to spread. Also, many studies lump all alien species, and fail to separate introduced, naturalized and invasive populations and species. These biases impede our ability to elucidate the full suite of drivers of invasion and to predict invasion dynamics, because different factors mediate progression along different sections of the continuum. A better understanding of the determinants of naturalization is important because all naturalized species are potential invaders. Processes leading to naturalization act differently in different regions and global biogeographical patterns of plant invasions result from the interaction of population-biological, macroecological and human-induced factors. We explore what is known about how determinants of naturalization in plants interact at various scales, and how their importance varies along the continuum. Research that is explicitly linked to particular stages of the continuum can generate new information that is appropriate for improving the management of biological invasions if, for example, potentially invasive species are identified before they exert an impact.
Keywords: populační dynamika; ekosystém; Population Dynamics; Ecosystem; biodiverzita; lidé; Biodiversity; vývoj rostlin; Geography; Introduced Species; zavlečené druhy; Plant Development; zeměpis; Humans